2016
DOI: 10.3390/coatings6030029
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for the Deposition of Bismuth Tungstate onto Titania Nanoparticulates for Enhancing the Visible Light Photocatalytic Activity

Abstract: Abstract:A novel powder handling technique was used to allow the deposition of bismuth tungstate coatings onto commercial titanium dioxide photocatalytic nanoparticles. The coatings were deposited by reactive pulsed DC magnetron sputtering in an argon/oxygen atmosphere. The use of an oscillating bowl with rotary particle propagation, positioned beneath two closed-field planar magnetrons, provided uniform coverage of the titania particle surfaces. The bismuth/tungsten atomic ratio of the coatings was controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The method provides such obvious advantages, in comparison to chemical methods, as; no requirement for toxic or hazardous precursors, an absence of hazardous process by-products, excellent control over uniformity and composition and great up-scaling potential. Despite the fact that magnetron sputtering is typically used for deposition of coatings onto flat substrates, the authors of the present paper have recently shown that it can be readily used for deposition of functional coatings onto particulates of various shapes and sizes, from several millimeters in diameter [4], to nanoparticulates [4,32].…”
Section: Introductionmentioning
confidence: 85%
“…The method provides such obvious advantages, in comparison to chemical methods, as; no requirement for toxic or hazardous precursors, an absence of hazardous process by-products, excellent control over uniformity and composition and great up-scaling potential. Despite the fact that magnetron sputtering is typically used for deposition of coatings onto flat substrates, the authors of the present paper have recently shown that it can be readily used for deposition of functional coatings onto particulates of various shapes and sizes, from several millimeters in diameter [4], to nanoparticulates [4,32].…”
Section: Introductionmentioning
confidence: 85%
“…The schematic representation of the setup is given elsewhere [20,21]. Bismuth and tungsten targets were fitted to these two magnetrons (both targets were 99.5% pure and bonded to copper backing plates).…”
Section: Deposition Processmentioning
confidence: 99%
“…As the substrates can range in size from several mm 2 to 6 m × 3 m "jumbo" sheets of architectural glazing, the deposition process is widely used for the production of various coatings, including photocatalysts, both in laboratory and industrial facilities. However, it is generally accepted that magnetron sputtering is predominately a "line of sight" process, best suited for the deposition of coatings onto flat substrates [20]. Nevertheless, the authors have recently successfully developed and reported a technology that enables the deposition of photocatalytic coatings onto substrates of "irregular" shape, such as powders and nanoparticles [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, photocatalysis technology appears as an efficient, economical, and environmental friendly technology, which can be applied in environmental remediation, as well as solar energy conversion, since it was discovered in 1972 [1][2][3]. To date, various types of semiconductor photocatalysts have been explored, especially the TiO 2 -based photocatalysts which are always being ranked as the most researched ones [4][5][6]. However, their applications are retarded by low ultilization efficiency for solar light absorption or a high recombination of charge carriers, thus making development of photocatalysts with visible light responsive ability indispensable.…”
Section: Introductionmentioning
confidence: 99%